Pengaruh Struktur Modal Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Melalui Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Sektor Energi Yang Terdaftar Di Bei Tahun 2020-2024 - Dina Atikah; Elfiswandi .; Putri Intan Permata Sari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the influence of capital structure and managerial ownership on profitability as an intervening variable in energy companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. This study employed a quantitative approach, with a purposive sampling method, resulting in a sample of 20 companies from a population of 100. The data used in this study were secondary data, consisting of annual data obtained from the official website of the Indonesia Stock Exchange and the official websites of related companies. The analytical method used in this study was multiple linear regression analysis with the assistance of SPSS 26. The results of the study showed that (1) capital structure partially had no effect on profitability, (2) managerial ownership partially had an effect on profitability, (3) capital structure partially had no effect on firm value, (4) managerial ownership partially had no effect on firm value, (5) profitability partially had an effect on firm value, (6) profitability was unable to mediate the effect of capital structure on firm value, and (7) profitability was able to mediate the effect of managerial ownership on firm value.